Infrared And Raman Spectroscopic And Quantum Chemical Investigations Of Zinc Halide Complexes Of 3-Aminoquinoline - Özel, Ayşen E.; Çelik, Sefa; Keçel, Serda; AKYÜZ, SEVİM (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2010)
In this study detailed structure and vibrational spectra of free and coordinated 3-AQ (3-AQ = 3-aminoquinoline; C(9)H(8)N(2)) have been reported. Vibrational wavenumbers of free 3-AQ its Zn halide complexes {Zn(3-AQ)(2)X(2); where X = Cl or Br} and 3-AQ interacting with water molecules have been calculated using a harmonic approach at B3LYP/6-31G(d,p) and B3LYP/6-31++G(d,p) theory levels. The wavenumbers of free 3-AQ have also been calculated using a harmonic approach at B3LYP/6-31++G(d,p) theory levels. The fundamental vibrational modes were characterized by their total energy distribution (TED%). The Zn(3-AQ)(2)X(2) complexes have been prepared for the first time and their vibrational wavenumbers were reported, in comparison with the calculated results. Coordination through the ring nitrogen effects on the vibrational wavenumbers of 3-AQ were investigated and the coordination sensitive modes of 3-AQ were determined. It was found that, the wavenumber-shifts due to complex formation depend on the halogen group and decreases in the order Cl > Br for the Zn(3-AQ)(2)X(2) complexes. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Density functional analysis (DFT); 3-Aminoquinoline; Zinc halide complexes; Vibrational wavenumbers; normal-coordinate analysis; vibrational-spectra; 8-aminoquinoline; assignments; Çinko-halojenür-kompleksleri; titreşim dalgasayıları; titreşim-spektrumları